2016
DOI: 10.1007/978-981-10-0575-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Model for the Gamification of Business Processes: A Study from the Field of Material Handling

Abstract: Gamification, as opposed to serious gaming, focuses on the integration of certain elements and mechanics from the field of gaming and game design into an existing (non-gaming) environment. Typical game design models do not meet the requirements of implementing a gamification application in total because they focus on the development of a holistic game. An implementation model for the gamification of business processes should focus on the integration of game elements and mechanics into an existing work context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Several approaches to evaluate a gamification design can be found in the literature. These range from quantitative to qualitative approaches [10,11,16,24,36] [7,10]. Several experts have highlighted that observing user behavior is more effective than interviewing, as users often have problems to describe experiences verbally [I7, I11, I18, I21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several approaches to evaluate a gamification design can be found in the literature. These range from quantitative to qualitative approaches [10,11,16,24,36] [7,10]. Several experts have highlighted that observing user behavior is more effective than interviewing, as users often have problems to describe experiences verbally [I7, I11, I18, I21].…”
Section: Discussionmentioning
confidence: 99%
“…We identified that due to the complexity, the selection of game-design elements and game mechanics is often more creative and brainstorming based in practice, than it is described in current literature [7] (e.g. [11,16,24,27,28,39]). Previously published methods often lack a detailed description of the creative ideation and design phase [5,11,24,27].…”
Section: Discussion Of the Research Findingsmentioning
confidence: 99%
See 3 more Smart Citations